Implementing Non-Formal Education through Marching Band Activities: Youth Artistic Competence at Makassar Drum Corps - Aan Rahdiyanzah; Sukarman B; Andi Ihsan (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Although arts education plays a crucial role in adolescent development, formal channels often lack the time and space for in-depth practice. In Makassar, there is a need for a non-formal educational platform capable of integrating technical aspects of the arts with holistic character development. This study aims to examine the implementation of non-formal education through marching band activities at Drum Corps Makassar (DCM) in developing adolescent artistic competencies covering the cognitive, affective, psychomotor domains, and identify the factors that influence them. This study used a qualitative approach with a case study design. Data was collected through participatory observation of the practice process, in-depth interviews with coaches, administrators, parents, and players, and a study of the training program documentation. Data were analyzed descriptively and interpretively using source triangulation to ensure the validity of the findings. The findings indicate that DCM serves as an effective non-formal educational institution. Cognitively, adolescents demonstrated increased musical literacy and visual-spatial problem-solving skills. Effectively, they developed strong characteristics of discipline, responsibility, and teamwork. Psychomotorically, there was significant improvement in motor coordination and instrument-playing techniques. This process is supported by a structured training system, intensive coaching guidance, and a supportive social environment (peer support). This research contributes to the strengthening of non-formal education theory, which suggests that community-based activities such as marching band can be an effective alternative learning model for developing artistic competence and character in adolescents outside of formal school.